EFFECT OF FISCAL DECENTRALIZATION ON CAPITAL EXPENDITURE, GROWTH, AND WELFARE - Rudy Badrudin (Economic Journal of Emerging Markets, 2011)
This research analyzes the influence of fiscal decentralization on capital expenditure, economic growth, and social welfare of 29 regencies and 6 cities in Central Java Province based on the data of year 2004 to 2008. The method used to analyze the hypotheses is the Partial Least Square. The results showes that fiscal decentralization has no significant effect on capital expenditure; fiscal decentralization has significant effect on economic growth and social welfare; capital expenditure has no significant effect on economic growth and social welfare; and economic growth has significant effect on social welfare.Keywords: Fiscal decentralization, capital expenditure, economic growth, social welfareJEL classification: H76, I31, 043